Evaluation of the VE1 Antibody in Thyroid Cytology Using Papillary Thyroid Carcinoma Specimens - Yon Hee Kim; Hyunee Yim; Yong-Hee Lee; Jae Ho Han; Kyi Beom Lee; Jeonghun Lee; Euy Young Soh; Seon-Yong Jeong; Jang-Hee Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background: Recently, VE1, a monoclonal antibody against the BRAFV600E mutant protein, has been investigated in terms of its detection of the BRAFV600E mutation. Although VE1 immunostaining and molecular methods used to assess papillary thyroid carcinoma in surgical specimens are in good agreement, evaluation of VE1 in thyroid cytology samples is rarely performed, and its diagnostic value in cytology has not been well established. In present study, we explored VE1 immunoexpression in cytology samples from ex vivo papillary thyroid carcinoma specimens in order to minimize limitations of low cellularity and sampling/targeting errors originated from thyroid fineneedle aspiration and compared our results with those obtained using the corresponding papillary thyroid carcinoma tissues. Methods: The VE1 antibody was evaluated in 21 cases of thyroid cytology obtained directly from ex vivo thyroid specimens. VE1 immunostaining was performed using liquid-based cytology, and the results were compared with those obtained using the corresponding tissues. Results: Of 21 cases, 19 classic papillary thyroid carcinomas had BRAFV600E mutations, whereas two follicular variants expressed wild-type BRAF. VE1 immunoexpression varied according to specimen type. In detection of the BRAFV600E mutation, VE1 immunostaining of the surgical specimen exhibited 100% sensitivity and 100% specificity, whereas VE1 immunostaining of the cytology specimen exhibited only 94.7% sensitivity and 0% specificity. Conclusions: Our data suggest that VE1 immunostaining of a cytology specimen is less specific than that of a surgical specimen for detection of the BRAFV600E mutation, and that VE1 immunostaining of a cytology specimen should be further evaluated and optimized for clinical use.